Substitute Blended Learning (SBL) Implementation Framework: A UNITEN Experience - Jamaluddin J.E.; Anuar A.; Ibrahim Z. (Springer Science and Business Media Deutschland GmbH, 2025)
This article presents the Substitute Blended Learning (SBL) Implementation Framework and its successful application at Universiti Tenaga Nasional (UNITEN). The SBL framework supports the need to enhance teaching and learning practices through the integration of online course delivery while ensuring a student-centered and engaging learning experience. The framework offers a comprehensive SBL model that is adaptable to UNITEN?s unique needs and to promote evidence-based practices for blended learning (BL). The application fills the gaps in the existing literature by providing a detailed account of the SBL implementation at UNITEN, as no prior similar work on SBL has been published. The SBL framework consists of 7 key steps, including conducting a thorough needs assessment, developing a comprehensive strategy, selecting appropriate tools and platforms, redesigning courses and curricula, providing faculty development programs, conducting pilot testing, refining the approach based on feedback, and finally, achieving full-scale implementation. Findings from the implementation reveal the successful integration of SBL into the pedagogical approach, enhancing flexibility, personalisation, and engagement for both lecturers and students. The SBL model also promotes effective learning outcomes by encouraging higher or-der thinking skills and fostering a deeper understanding of course content. This article contributes valuable insights and practical guidelines for institutions seeking to implement SBL strategies effectively, thus advancing the adoption of digital technology in higher education. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.